The Health Burden of E-Waste: The Impact of E-Waste Dumping Sites on Child Mortality - Stefania Lovo; Samantha B. Rawlings (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper examines the effect of e-waste dumping sites on early child health. We focus on two major dumping sites in West Africa, in Ghana and Nigeria. We observe children born before and after the creation of these dumps, and estimate a difference-in-difference specification in which we compare outcomes of those born within the vicinity of the dump to those farther away, before and after e-waste sites were created. We find that the e-waste sites increase neonatal and infant mortality, for children living in the proximity of the site. Event studies suggest that the negative effects emerge 2-3 years after the existence of the sites, consistent with the gradual and systematic build up of contaminants in the environment. By exploring routes of exposure, we find that the contamination of water and urban farming produce are among the drivers of the observed effects.
Keywords: I10; Q53; Q56; O10; 330; E-waste; health; infant mortality; dumping sites; West Africa